Perbandingan Tebal Perkerasan Menggunakan Nilai CBR Laboratorium dan CBR Lapangan (DCP) (JLS Jarit-Puger) - Alvina Praha Laili; Akhmad Hasanuddin; Luthfi Amri Wicaksono (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2022)
CBR (California Bearing Ratio) data is used to find out the level of subgrade density, so that a safe pavement thickness can be planned. The calculation of the CBR (California Bearing Ratio) can be done by testing CBR laboratory and DCP. CBR results have a high effect on the surface layer, so that the layer becomes thinner. This condition, if converted to the working price, will be more affordable and efficient. Therefore, this study aims to compare the results of laboratory CBR and Field Cbr (Dcp) to the thickness of flexible pavements in the Development of Trans South-South Java Road Project (TRSS) Lot 8 Jarit - Puger. The method used is Bina Marga Pd T-01-2002-B. Secondary data obtained by weigh bridges and service providers, namely PT. Brantas Abipraya (Persero). Field CBR value using DCP tool is 25.19% while Laboratory CBR value is 21.616%. The results of pavement thickness using Field CBR values ​​for UR 10 years are D1 7.5 cm, D2 10cm, for UR 20 years D1 10 cm, D2 11 cm, for UR 30 years D1 11 cm, D2 12 cm, and for UR 40 years obtained D1 13 cm, D2 14 cm. The greater the CBR value, the thinner the pavement thickness.